Forschungsfeld Sprachevolution Methodik, Theorie und Empirie der modernen Sprachursprungsforschung - Breyl, Michael (Linguistik - Impulse & Tendenzen, 2021)
This book provides a comprehensive and innovative exploration of the heterogenous field of linguistic evolution. The introductory sections discuss its subject-specific and methodological foundations. The main focus is the development and application of (meta)scientific methods for the systematic reception of the interdisciplinary research landscape. This volume analyses the methodology, theory and empiricism of various disciplines and fields.